The Rape of Europa in Ancient Literature - Reeves, Bridget T. (My University, 2003)
This thesis considers how ancient authors narrate the story of Europa's rape in such a way as to "place their own mark" on the myth. In chapter one, I explore aspects of the Europa myth that often do not appear in the larger extent works such as Europa's function in religion, the archaeological representations of her rape, and the rationalization of the myth etc. Chapter two provides the audience with the basic outline of the story so that it will be equipped to appreciate the changes each writer makes to the story. As well, the development of the Europa myth over time is considered here. Outlined in chapter three is the approach (i.e. the use of traditional and new tools of literary criticism) I take to investigate the works offered by the ancient writers, beginning first with Moschus' account. An appreciation of the techniques Moschus incorporates is presented in chapter three while in chapter four the poet's elaboration of the ekphrasis and the inclusion of an embedded narrative are examined. The next three chapters (5, 6, and 7) look at Horace's and Ovid's (two) treatments of the rape of Europa, and chapter eight focusses on the versionf of later Greek writers, Achilles Tatius, Lucian and Nonnos. Finally, in chapter nine conclusions are made about the various rape narratives of Europa, especially about trends in the myth's treatments, links and contrasts between versions, and the variety which each writer adds with regard to form, description, tone and characterization. This investigation sheds new light on how ancient authors, when faced with a long tradition of myth telling, go about creating a fresh and entertaining story.
Keywords: Classics; Classics